The Interconnectedness of Takwa (God-Consciousness) and Cardiac Health: An Integrative Analysis of Qur’anic and Hadith Perspectives - Suseno, Andi; Islahuddin (MADINAH, 2025)
This study reveals the relationship between takwa and heart health in humans based on the Qur'an and hadith. Islamic law was revealed by Allah to bring benefits to human life, not only for the hereafter but also for this world. The research method used was qualitative with an integration-interconnection approach with a unified scientific perspective. Research on the Qur'an and hadith informs us that takwa in the human body is located in the chest, namely the heart. The quality of takwa has a significant correlation with heart health. The correlation between takwa and heart health is demonstrated based on both the characteristics of takwa and the activities that shape takwa. The conclusion is that a person's level of takwa has an impact on their heart health. The higher a person's level of takwa, the healthier their heart will be, both as the center of emotions and as the center of the human body's organs. Further research is needed in a more measurable form, both in terms of mechanisms and psychological and health implications.